2017
DOI: 10.12945/j.jshd.2016.005.16
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Atrial Septal Defect Occlusion

Abstract: We present 11 cases of percutaneous transcatheter occlusion of atrial septal defects (ASDs) in adults, including multi-fenestrated ASD, balloon-assisted deployment of ASD occlude, dilator-assisted deployment of ASD occlude, "cobra"-shaped disfiguration of the left disc, ASD with deficient aortic rim, pulmonary vein-assisted deployment of ASD occlude, "high" ASD, large Chiari network, double interatrial septum, snaring a runaway occluder, and right ventricular diastolic dysfunction causing cyanosis. Each case i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…2 Deficient aortic rim has been associated with increased risk of device impingement on the aorta. 8 Ostermayer et al found that small aortic rim is independently associated with procedural failure. 9 On the other hand, O'Byrne et al found that deficient aortic rim is highly prevalent but does not seem to increase the risk of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…2 Deficient aortic rim has been associated with increased risk of device impingement on the aorta. 8 Ostermayer et al found that small aortic rim is independently associated with procedural failure. 9 On the other hand, O'Byrne et al found that deficient aortic rim is highly prevalent but does not seem to increase the risk of adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%